Projects-Based Mid-Assessment Model of English at the Junior High School Grade 7 - Citrayasa, Vinindita (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2015)
This article offers a project-based model of mid-term assessment for junior high school gradeseven. The model was proposed to help English teachers in assessing their students‟ learningprocess and learning results according to Curriculum 2013. English teachers still finddifficulty creating an authentic and holistic assessment due to the time limitation. Theresearch questions are first, whatthe model of project-based mid-term assessment of Englishat the junior high school grade 7 look likes and second, how the project-based mid-termassessment support teachers to conduct mid-term assessment. Thisis R & D research, which has two goals: the research goal and project goal. First, theresearch goal is to present the iconic model version of authentic mid-term assessment ofEnglish learning. The project goal is to develop the authentic mid-term assessment of Englishlearning for junior high school students and to understand the teachers‟ perceptions of thisassessment. The results of the pilot study showed that this model was authentic and holistic.However the proposed model still needs revisions in order to become more effective inassessing students‟ learning process.Keywords: assessment model, project-based, senior junior high school